2020
DOI: 10.1111/pai.13388
|View full text |Cite
|
Sign up to set email alerts
|

IL‐1 signaling pathway molecules as key markers in childhood asthma

Abstract: Objective The prevalence of childhood asthma has been increasing in recent years. This study aims to investigate the involvement of the key molecules of IL‐1 (interleukin‐1) signaling pathways in pediatric patients with asthma. Methods Differentially expressed genes (DEGs) associated with IL‐1 signaling pathways were identified with RNA‐seq from peripheral blood samples collected from asthmatic or healthy children and were further verified in clinical peripheral blood samples. Cellular models and asthmatic mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…As a caspase‐regulated process, pyroptosis mediates airway epithelial cell death 41 and pro‐inflammatory responses in lung macrophages 42 . Recently Wei et al 43 . observed increased expression levels of genes involved in IL‐1 signaling pathway (IL‐1RN, IL‐1RAP, IRAK3, and PELI1) in children with persistent asthma and those with acute asthma exacerbation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a caspase‐regulated process, pyroptosis mediates airway epithelial cell death 41 and pro‐inflammatory responses in lung macrophages 42 . Recently Wei et al 43 . observed increased expression levels of genes involved in IL‐1 signaling pathway (IL‐1RN, IL‐1RAP, IRAK3, and PELI1) in children with persistent asthma and those with acute asthma exacerbation.…”
Section: Discussionmentioning
confidence: 99%
“…40 As a caspase-regulated process, pyroptosis mediates airway epithelial cell death 41 and pro-inflammatory responses in lung macrophages. 42 Recently Wei et al 43 observed increased expression levels of genes involved in IL-1 signaling pathway (IL-1RN, IL-1RAP, IRAK3, and PELI1) in children with persistent asthma and those with acute asthma exacerbation. Despite evidence for IL-1 signaling in our gene expression data, we observed a lack of IL-1α and IL-1β protein levels in plasma which may be attributed to increased IL-1RA protein levels.…”
Section: Currently Associations Between Gene Expression Patterns Inmentioning
confidence: 99%
“…IL1RAP mRNA is increased in PBMCs from children with asthma compared with healthy controls, and its expression is enhanced with increasing asthma severity and during exacerbations. 44 Selective blocking of IL1RAP with a monoclonal antibody (mAB‐mR3) inhibits signalling not only by IL‐33 but also IL‐1 and IL‐36 pathways. 45 In an ovalbumin‐driven murine model of asthma, MAB‐mR3 reduced lung neutrophilia as well as suppressing eosinophilia.…”
Section: Discussionmentioning
confidence: 99%
“…However, chymase also induced release of the anti-inflammatory factor IL-1RA. Considering that IL-1 signaling has been implicated in asthma, 35,36 IL-1RA induction by chymase could have a regulatory role by downregulating the effects of IL-1 under such circumstances. Hence, chymase induces both proinflammatory and antiinflammatory compounds in HSAECs, and whether the effects of chymase on the airway epithelial cells result in an altogether proinflammatory or anti-inflammatory outcome is thus not certain.…”
Section: Discussionmentioning
confidence: 99%